2012
DOI: 10.1002/hyp.9251
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of climate natural variability in water resources evaluation impacted by climate change

Abstract: Water resource assessment on climate change is crucial in water resource planning and management. This issue is becoming more urgent with climate change intensifying. In the current research of climate change impact, climate natural variability (fluctuation) has seldom been studied separately. Many studies keep attributing all changes (e.g. runoff) to climate change, which may lead to wrong understanding of climate change impact assessment. Because of lack of long enough historical series, impacts of climate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Liu et al (2012) make the salient point that many climate change impact assessment studies start from the position that impacts are attributable to GHG-induced climate change only, and do not properly account for natural climatic variability. Using seven future climate projections derived from three GCMs and three emission scenarios, the impact of future climate change on water resources was estimated in terms of separating its contribution from natural climatic variability.…”
Section: Evidence For Climate Change Impacts On the Hydrological Cyclmentioning
confidence: 99%
“…Liu et al (2012) make the salient point that many climate change impact assessment studies start from the position that impacts are attributable to GHG-induced climate change only, and do not properly account for natural climatic variability. Using seven future climate projections derived from three GCMs and three emission scenarios, the impact of future climate change on water resources was estimated in terms of separating its contribution from natural climatic variability.…”
Section: Evidence For Climate Change Impacts On the Hydrological Cyclmentioning
confidence: 99%
“…They mainly aim on decomposition the GCMs, emission scenarios, downscaling method, hydrological model structure and parameter for simulation process (Kujawa et al 2020;Shi et al 2020;Keller et al 2019). Moreover, to investigate the role of the internal variability in the overall climate change uncertainty can provide more useful information to uncertainty estimating of simulation process and establish more comprehensive framework of uncertainty analysis (Liu et al 2012;Xue et al 2014;Yen et al 2014;Schindler et al 2015;Steinschneider et al 2015;Nerantzaki et al 2020). (Belcher et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at present, there are many studies regarding the climate change over major rivers in China (Li et al ., 2008; Zhang et al ., 2009; Bao et al ., 2012; Liu et al ., 2012; Wang, Zhang, et al, 2012; Wang, Sun, et al, 2012; Yin et al ., 2016). Most of them have used global climate models (GCMs), for example, based on five GCMs, Yin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at present, there are many studies regarding the climate change over major rivers in China (Li et al, 2008;Zhang et al, 2009;Bao et al, 2012;Liu et al, 2012;Wang, Sun, et al, 2012;Yin et al, 2016). Most of them have used global climate models (GCMs), for example, based on five GCMs, Yin et al (2016) indicated that the extreme precipitation over most of HHH river basin will increase considerable in the future, which will result in larger flood risk.…”
Section: Introductionmentioning
confidence: 99%